Molecular dynamics simulation of uranium nitride oxidation - Galashev Alexander Y.; Zaikov Yurii P.; Abramova Kseniya A.; Rakhmanova Oksana R.; Mochalov Yurii S. (Journal of the Serbian Chemical Society)
A molecular dynamic simulation of the uranium mononitride (UN) oxidation in an Ar–O medium in the temperature range of 373–2073 K is performed. The study is performed for UN particles with a crystalline and amorphous structure at an oxygen concentration in the gas mixture of 22.5 mol. %. The most efficient oxidation for an amorphous particle occurs at lower temperatures than that for a crystalline particle. Unlike crystalline fragments, amorphous particles undergo more severe fragmentation when they bind to oxygen. Fragmentation of UN particles is one of the main factors regulating the oxidation of finely dispersed media. The oxidation of a UN particle begins from its surface and in the case of an amorphous particle occurs faster than when the particle is crystalline. The process of particle fragmentation is facilitated by the penetration of oxygen atoms inside the particle. An increase in the oxygen concentration in the gas mixture stimulates the oxidation process. The structural changes in the system are investigated by constructing the partial radial distribution functions. The many-body U–N interactions prevent nitrogen escaping into the gaseous environment.